PROGRAM INOVASI “SIMARA” SEBAGAI UPAYA PENCEGAHAN DAN DETEKSI DINI INFEKSI MENULAR SEKSUAL PADA REMAJA - Novianti, Wida; Kim Jiu, Cau; Jimmy Pintabar, Andar (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Sexually Transmitted Infections (STIs) are one of the public health problems that have a significant impact on the quality of life of individuals and communities, especially in adolescent groups. Sintang Regency, especially the working area of ​​Tanjung Puri Health Center, faces serious challenges related to the high incidence of STIs. This situation requires innovative and integrated interventions to increase awareness, encourage prevention, and facilitate early detection of STIs among adolescents. The purpose of this community service is to develop a web/android-based adolescent reproductive health education application. The results of the application trial showed that 85% of adolescents felt helped by the self-assessment feature in recognizing the risk of STIs. As many as 70% of respondents admitted to getting new information about reproductive health and knowledge about STIs through the application. Health workers stated that the application facilitates the process of data monitoring, adolescent screening and networking programs and provides referrals to high-risk users. Conclusion The creation of an innovation program in the form of a screening application for Sexually Transmitted Infections (STIs) in adolescents, named SIMARA (Information and Monitoring System for STIs in Adolescents) is a strategic step to support efforts to prevent and detect early STIs at the Tanjung Puri Sintang Health Center